Efektifitas ACBT Dalam Meningkatkan Ekspansi Dada Pada Kasus Bronchiectasis : Studi Kasus - ﻿Pahlawi, ﻿Riza; ﻿Pratama, ﻿Aditya ﻿Denny; Noviana, Mita; ﻿Iskandar, ﻿Anastasia ﻿Viastuti (Jurnal Fisioterapi Terapan Indonesia, 2022)
Bronchiectasis is a major chronic disease characterized by infection, inflammation, and permanent dilation of the bronchial walls. Interaction of chronic infection, exacerbation, and inflammation resulting in lung injury. Patients with bronchiectasis have several clinical manifestations of primary bronchiectasis, which is the occurrence of recurrent, chronic infections. In patients with bronchiectasis, mechanical efficiency of breathing leads to decreased rib movement and increased abdominal movement leading to a paradoxical breathing pattern. Treatment goals include achieving symptom control, preventing or reducing exacerbations. Various alternative airway techniques have been used in the physiotherapeutic management of patients with bronchiectasis. Techniques are considered the way to be considered an integral component of management. The breathing technique consists of an intermediary that regulates breathing control, hard expansion exercises. ACBT (Active Cycle Breathing Technique) is an intervention that aims to improve the condition of the chest wall. ACBT has a significant effect on the rate of chest expansion. So that these interventions can increase chest expansion and can reduce fatigue in taking a breath.. The therapist does not huff because the patient can cough effectively. In addition to increasing chest expansion, the effectiveness of ACBT is also useful for reducing shortness of breath, reducing phlegm, and exacerbations. Appropriate ACBT can also exacerbation of symptoms and reduce patient morbidity and mortality. Because of its effectiveness, it is preferred by the patient and if the cost is really enjoyed by the patient, it can be done at home. Other airway treatments have also shown benefit for the treatment of bronchiectasis, but ACBT shows a great effect on symptoms.1 ACBT has a significant effect in improving airways and improving lung function in bronchiectasis, but ACBT has a better effect on improving airways.